Additive for diamond wire composite electroplating second-phase particles, electroplating solution containing additive and preparation method of electroplating solution

By adding specific additives to the electroplating solution and optimizing the electroplating solution formula, the problem of slow sanding speed and uneven distribution of diamond wire composite electroplating is solved, and the rapid and uniform sanding and stable production of diamond particles is achieved.

CN119121335APending Publication Date: 2024-12-13YANGLING METRON NEW MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411313537.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

In the prior art, diamond wire composite electroplating has a slow sand speed and uneven particle distribution, which cannot meet the actual production needs.

Method used

Add 3,3,4,4-tetramethylpyrrolidine-2,5-dione, polyethylene glycol, isodecanol polyoxyethylene ether, polyacrylamide and other additives to form aminosulfonium Nickel acid nickel plating system optimizes the formulation and process parameters of the electroplating solution, and improves the sanding speed and uniformity.

Benefits of technology

It realizes rapid and even sanding of diamond particles, stabilizes large-scale production of diamond wires, and improves product quality and production efficiency.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119121335A_ABST
    Figure CN119121335A_ABST
Patent Text Reader

Abstract

The invention relates to an additive for diamond wire composite electroplating second-phase particles, electroplating liquid containing the additive and a preparation method of the electroplating liquid. The additive is prepared from 3, 3, 4, 4-tetramethyl pyrrolidine-2, 5-diketone, polyethylene glycol, triethanolamine, polyacrylamide, glycine, hexadecyl trimethyl ammonium chloride, octadecyl trimethyl ammonium bromide, sodium dodecyl benzene sulfonate, pyridinium hydroxypropane sulfonate, polyallylamine hydrochloride, isodecyl alcohol polyoxyethylene ether, fatty alcohol polyoxyethylene ether and sodium benzoate, and the solvent is a solvent. The additive is one or more of polydimethyldiallylammonium chloride, polyvinyl alcohol, diethylene glycol, aluminum potassium sulfate dodecahydrate and dibenzenesulfonimide. The electroplate liquid comprises 250-540 g / L of nickel aminosulfonate, 2-35 g / L of nickel chloride, 0.5-15 g / L of basic nickel carbonate, 30-45 g / L of boric acid, 0-5 g / L of saccharin and the additive, the pH value of the electroplate liquid is 3.5-5.3, and the electroplate liquid further comprises the additive, and through selection and compounding of the multiple additives, sand can be rapidly and evenly fed, and the diamond wires can be stably produced in a large scale.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of electroplating, and in particular to an additive for diamond wire composite electroplating second phase particles, an electroplating solution containing the additive, and a preparation method thereof. Background Art

[0002] The production of diamond wire saws generally uses a composite electroplating method to deposit diamond and other hard material particles on metal wires such as steel wire and tungsten wire. In this process, the speed and uniformity of the deposition of diamond particles (sand) on the metal wire (called sanding) are crucial to reducing the manufacturing cost of diamond wire, improving product quality, and improving the cutting quality and efficiency of cutting objects. In order to improve the speed and uniformity of diamond particles deposited on the metal wire (sanding), various measures can be adopted, such as optimizing the main formula of the electroplating solution, optimizing the process parameters such as current, voltage, and temperature, improving the surface state of the diamond (using metallized diamond particles and treating the surface), and improving the production line.

[0003] Even if these measures are used in production, there are still situations where the production speed and uniformity of diamond particles are poor and cannot meet the actual production needs; for this reason, a method of adding a very small amount of chemical substances that can improve the speed and uniformity of sanding to the electroplating solution, which is called an additive, begins to be used. Although the choice of additives can be varied, there are not many additives that have excellent improvement effects and stable performance so that diamond wires can be produced on a large scale. For this reason, the present invention specifically provides additives for diamond wires that can be used efficiently, stably and on a large scale. At the same time, in order to use these additives more effectively, it is necessary to adjust and optimize the electroplating solution in the sanding process. Therefore, the present invention also specifically describes the relevant electroplating solution formula and preparation method. It should be pointed out that these additives are used in conjunction with the electroplating solution formula and need to be optimized according to production requirements and process conditions. Summary of the invention

[0004] The purpose of the present invention is to overcome the problems of slow sanding speed and local agglomeration of sand in diamond wire composite electroplating in the prior art, and to provide an additive for second phase particles in diamond wire composite electroplating, an electroplating solution containing the additive, and a preparation method thereof. The present invention adds the additive of the present invention to the main electroplating solution to achieve the purpose of increasing the sanding speed and uniform sanding.

[0005] To achieve the above object, the technical solution adopted by the present invention is:

[0006] An additive for diamond wire composite electroplating second phase particles, the additive is one or more of 3,3,4,4-tetramethylpyrrolidine-2,5-dione, polyethylene glycol, triethanolamine, polyacrylamide, glycine, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, hydroxypropanesulfonic acid pyridinium salt, polyacrylamine hydrochloride, isodecanol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sodium benzoate, polydimethyldiallylammonium chloride, polyvinyl alcohol, diethylene glycol, potassium aluminum sulfate dodecahydrate, and diphenylsulfonimide. The additive is added to the main electroplating solution of the present invention and mixed evenly before use.

[0007] The invention discloses an electroplating solution containing the additive, wherein the electroplating solution is a nickel sulfamate nickel plating system, and the formula thereof is as follows: nickel sulfamate content is 250-540 g / L, nickel chloride content is 2-35 g / L, basic nickel carbonate content is 0.5-15 g / L, boric acid content is 30-45 g / L, saccharin content is 0-5 g / L, pH value is 3.5-5.3, and the content of the additive in the electroplating solution is 0-0.6%.

[0008] Furthermore, the diamond wire is one of steel wire, tungsten wire and carbon fiber, and the wire diameter does not exceed 2000 μm.

[0009] Furthermore, the second phase particles are non-metallized particles including diamond, SiC, and cubic boron nitride, and metallized particles obtained by metallizing the non-metallized particles. Non-metallized particles including diamond, SiC, and cubic boron nitride refer to particles having very poor electrical conductivity and being insulators; metallized particles including diamond, SiC, and cubic boron nitride refer to particles including diamond, SiC, and cubic boron nitride whose surface or entirety is conductive (semiconductor) or have a certain conductive (semiconductor) coating layer. The metallized particles including diamond, SiC and cubic boron nitride can be metallized particles including diamond, SiC and cubic boron nitride coated with metal or conductive polymer or other conductive layer by chemical electrodeposition, plasma discharge or other methods; they can also be graphitized and coated with graphene to make the surface of particles including diamond, SiC and cubic boron nitride conductive by, for example, CVD method or heating method; they can also be particles including diamond, SiC and cubic boron nitride that are conductive as a whole, for example, by adding boron, nitrogen element or metal substance; the above methods can also be mixed to make non-metallized particles become metallized particles.

[0010] Furthermore, the additive is polyacrylamine hydrochloride, accounting for 0%-0.5% by weight.

[0011] Furthermore, the additive is 3,3,4,4-tetramethylpyrrolidine-2,5-dione, accounting for 0%-0.5% by mass.

[0012] Furthermore, the additive is composed of isodecanol polyoxyethylene ether, diethylene glycol and polydimethyldiallylammonium chloride.

[0013] The mass percentage of isodecanol polyoxyethylene ether is 0%-0.2%;

[0014] The mass percentage of diethylene glycol is 0%-0.1%;

[0015] The mass percentage of polydimethyldiallylammonium chloride is 0%-0.5%.

[0016] Furthermore, the additive is composed of hydroxypropane sulfonic acid pyridinium salt and fatty alcohol polyoxyethylene ether.

[0017] Hydroxypropane sulfonic acid pyridinium salt accounts for 0%-0.2% by mass;

[0018] The mass percentage of fatty alcohol polyoxyethylene ether is 0%-0.1%.

[0019] Furthermore, the additive is composed of polyacrylamine hydrochloride and fatty alcohol polyoxyethylene ether.

[0020] Polyacrylamine hydrochloride accounts for 0%-0.25% by mass;

[0021] The mass percentage of fatty alcohol polyoxyethylene ether is 0%-0.5%.

[0022] Furthermore, the additive is composed of polyacrylamine hydrochloride, fatty alcohol polyoxyethylene ether and polydimethyldiallylammonium chloride.

[0023] Polyacrylamine hydrochloride accounts for 0%-0.6% by mass;

[0024] Fatty alcohol polyoxyethylene ether accounts for 0%-0.3% by mass;

[0025] The mass percentage of polydimethyldiallylammonium chloride is 0%-0.5%.

[0026] Furthermore, the additive is composed of octadecyltrimethylammonium bromide, polyethylene glycol and isodecanol polyoxyethylene ether.

[0027] Octadecyltrimethylammonium bromide accounts for 0%-0.2% by mass;

[0028] Polyethylene glycol accounts for 0%-0.2% by mass;

[0029] The mass percentage of isodecanol polyoxyethylene ether is 0%-0.5%.

[0030] Furthermore, the additive is composed of potassium aluminum sulfate dodecahydrate, triethanolamine, sodium benzoate and fatty alcohol polyoxyethylene ether.

[0031]

[0032] A method for preparing an electroplating solution containing the additive comprises the following steps:

[0033] (1) dissolving the additive into an additive solution;

[0034] (2) Add nickel sulfamate and nickel chloride into deionized water at 55-70° C., and heat and stir until they are completely dissolved;

[0035] (3) heating boric acid and deionized water to 70-90° C., stirring while heating until all are dissolved, and then pouring the boric acid solution into the dissolved nickel solution in (2) and stirring evenly;

[0036] (4) Take basic nickel carbonate and deionized water, stir while heating for 5 minutes, then filter and add the filtered solution to the solution prepared in (3);

[0037] (5) Add saccharin to the solution prepared in (4), heat to 55-70° C., and stir while heating until completely dissolved;

[0038] (6) adjusting the pH value with ammonia and aminosulfonic acid, and then adding deionized water to the required amount of plating solution to control the pH value to 3.5-5.3; the preferred pH value range is 4.65-4.85;

[0039] (7) Add the additive solution to the electroplating solution prepared in (6), and stir while heating until the mixture is uniformly mixed to prepare an electroplating solution containing the additive.

[0040] Compared with the prior art, the present invention has the following beneficial effects:

[0041] The invention achieves the purpose of being able to quickly and evenly sand and stably produce diamond wires on a large scale through the selection and compounding of a variety of additives. BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Example 1, magnified 400 times.

[0043] Figure 2 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Comparative Example 1, magnified 400 times.

[0044] Figure 3 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Comparative Example 2, magnified 400 times.

[0045] Figure 4 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Comparative Example 3, magnified 400 times.

[0046] Figure 5 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Example 2, magnified 400 times.

[0047] Figure 6 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Example 3, magnified 400 times.

[0048] Figure 7 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Comparative Example 4, magnified 400 times.

[0049] Figure 8 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Comparative Example 5, magnified 400 times.

[0050] Fig. 9 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Example 4, magnified 400 times.

[0051] Fig.10 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Example 5, magnified 400 times.

[0052] Fig.11 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Example 6, magnified 400 times.

[0053] Fig.12 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Example 7, magnified 400 times.

[0054] Fig.13 This is an optical microscope image of the surface coating of the diamond wire saw prepared in Example 8, magnified 400 times. DETAILED DESCRIPTION

[0055] The present invention is described in detail below in conjunction with specific embodiments, but it is also explained that the protection scope of the present invention is not limited to the specific scope of the present embodiment, and all other embodiments obtained by ordinary technicians in the field without making creative work based on the embodiments of the present invention are within the scope of protection of the present invention.

[0056] Example 1

[0057] The formula of the sand plating solution in this embodiment is: 350g / L nickel sulfamate, 35g / L nickel chloride, 8g / L basic nickel carbonate, 35g / L boric acid, 0.5g / L saccharin, 12.5mg / L additive polyacrylamine hydrochloride; pH value is 4.8.

[0058] In this embodiment, a steel wire with a diameter of 120 μm is selected as the diamond wire, a metallized diamond particle coated with a nickel layer is selected as the second phase particle, the content of the metallized diamond particle is 1 g / L, and the electroplating liquid system configured in Example 1 is used for the electroplating process. The mechanical stirring speed of the plating liquid is set to 420 r / min, the plating liquid temperature is 65°C, and the cathode current density is 8.2 A / dm 2 The time for sand plating is 1min, and the time for thickening plating is 20s.

[0059] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Figure 1 As shown by Figure 1 It can be seen that the coating is smooth and bright overall, and there are still a few points where the metallized diamond particles coated on the surface of the diamond wire are agglomerated. Overall, the amount of sanding is large, and the distribution uniformity of the metallized diamond particles on the surface of the diamond wire is good.

[0060] Comparative Example 1

[0061] The same operation as in Example 1 was performed except that non-metallized diamond particles were used instead of the second phase particles in Example 1.

[0062] The surface morphology of the diamond wire prepared according to Comparative Example 1 is as follows: Figure 2 As shown by Figure 2 It can be seen that the surface coating of the diamond wire is smooth and bright. Due to the uneven dents on the diamond wire itself and the dents not completely eliminated after the coating, two smaller dents can be observed. In fact, the metallized diamond particles used in Example 1 and the non-metallized diamond particles used in Comparative Example 1 have different specifications. Figure 1 It can be seen that the non-metallized diamond particles in Comparative Example 1 are smaller in size, and the non-metallized diamond particles themselves have poor conductivity, and the surface is almost exposed without nickel plating. Overall, the diamond wire prepared in Comparative Example 1 has a large amount of sand, and the plated non-metallized diamond particles rarely agglomerate and have good distribution uniformity.

[0063] Comparative Example 2

[0064] The same operation as in Example 1 was carried out except that the polyacrylamine hydrochloride in the plating solution of Example 1 was removed.

[0065] The surface morphology of the diamond wire prepared according to Comparative Example 2 is as follows: Figure 3 As shown by Figure 3It can be seen that when the diamond wire is prepared without using any of the additives, the metallized diamonds coated on the surface are almost all in a state of agglomeration, the particle distribution uniformity is very poor, and the brightness of the diamond wire coating prepared in Comparative Example 2 is relatively dark. Figure 1 In comparison, it can be shown that the additive described in Example 1 has a greater effect on improving the uniformity of metallized diamond sanding and improving the sanding quality.

[0066] Comparative Example 3

[0067] The same operation as in Example 1 was performed except that the polyacrylamine hydrochloride in the electroplating solution in Example 1 was removed and non-metallic diamond particles were used instead of the second phase metallized particles in Example 1.

[0068] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Figure 4 As shown by Figure 4 It can be seen that the surface of the prepared diamond wire is almost not coated with diamond particles. Figure 2 It can be seen that without using the additives described in Comparative Example 1, it is very difficult to sand the non-metallized diamond.

[0069] The hydrophilicity, Zeta potential and amount of sand applied to the electroplating systems in Example 1 and Comparative Examples 1 to 3 were tested.

[0070] The hydrophilicity test is as follows: the second phase particles are immersed in the upper sand plating solution for 1-2 hours to obtain a suspension containing the second phase particles; the suspension containing the second phase particles is sampled and measured using a contact angle tester.

[0071] The Zeta potential test is as follows: filtering and drying the suspension containing the second phase particles, dispersing the obtained second phase particles in deionized water to form a suspension, and then measuring the Zeta potential.

[0072] The sanding amount detection is as follows: under an optical microscope, 8 positions are randomly selected to take pictures of the coating surface of the prepared wire saw at a magnification of 400 times, and the number of sanding particles is counted to calculate the sanding amount per unit length of the diamond wire saw prepared above; and the average value of the 8 groups of counts is taken, and the result is retained as an integer.

[0073] The results of Example 1 and Comparative Examples 1 to 3 are summarized in Table 1. Figure 1-4 shown.

[0074] Table 1 Comparison of hydrophilicity, zeta potential, amount of sand, and state of sand in Example 1 and Comparative Examples 1 to 3

[0075] Hydrophilicity(°) Zeta potential (mV) Sand quantity (grains / cm) Sanding status Example 1 61 23 475 Good uniformity Comparative Example 1 57 20 331 Good uniformity Comparative Example 2 63 15 - More reunions Comparative Example 3 59 13 0 Difficulty in sanding

[0076] It can be concluded from Table 1 that when the additive of Example 1 of the present invention is not used, it is very difficult for the bare diamond sand particles to be sanded on the surface of the wire saw after electroplating with the nickel sulfamate electroplating solution. Through observation, when the additive of Example 1 of the present invention is not used, the distribution uniformity of the metallized diamond particles on the surface of the diamond wire is poor, and it is very difficult to count the amount of sand due to the presence of many nodular agglomerates. When the additive of Example 1 of the present invention is used, the hydrophilicity and Zeta potential of the bare diamond sand particles and the metallized diamond particles in the electroplating solution are improved, and the average amount of sand on the surface of the diamond wire for the bare diamond sand particles is 331 grains / cm. The average amount of sand on the surface of the wire saw for the metallized diamond particles is 475 grains / cm. Through observation, when the additive of Example 1 of the present invention is used, Figure 1 It can be seen that the agglomeration of the metallized diamond particles on the surface of the wire saw is reduced, which shows that when the additive of Example 1 of the present invention is used, the distribution uniformity of the metallized diamond particles on the surface of the wire saw obtained by electroplating is better.

[0077] Example 2

[0078] The same operation as in Example 1 was carried out except that the additive in Example 1 was replaced with 3,3,4,4-tetramethylpyrrolidine-2,5-dione in a content of 25 mg / L.

[0079] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Figure 5 As shown by Figure 5 It can be seen that the overall coating of the diamond wire is smooth and bright, there is a lot of sand on the surface of the diamond wire, and the plated metallized diamond particles have no obvious agglomeration. However, there are local areas on the surface of the diamond wire where the plated metallized diamond particles are relatively sparse. Overall, the distribution uniformity of the metallized diamond particles on the surface of the diamond wire is average.

[0080] Example 3

[0081] The additives in Example 1 were replaced with a composite additive formula consisting of isodecanol polyoxyethylene ether, diethylene glycol and polydimethyldiallyl ammonium chloride, wherein the content of isodecanol polyoxyethylene ether was 2.5 mg / L, the content of diethylene glycol was 7.5 mg / L, the content of polydimethyldiallyl ammonium chloride was 12.5 mg / L, and the molecular weight of polydimethyldiallyl ammonium chloride was 100,000. Other than this, the same operations were performed as in Example 1.

[0082] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Figure 6 As shown by Figure 6 It can be seen that the coating is smooth and bright overall, with a large amount of sand, almost no particle agglomeration, and the metallized diamond particles on the surface of the diamond wire have excellent distribution uniformity.

[0083] Comparative Example 4

[0084] The pH value of the electroplating solution of Example 3 is adjusted to 4.0 by reducing the content of basic nickel carbonate and adding an appropriate amount of aminosulfonic acid. Otherwise, the operation is the same as that of Example 3. The formula of the electroplating solution of this embodiment is as follows: the content of nickel aminosulfonate is 350 g / L, the content of nickel chloride is 35 g / L, the content of basic nickel carbonate is 7.45 g / L, the content of aminosulfonic acid is 0.25 g / L, the content of boric acid is 35 g / L, the content of saccharin is 0.5 g / L, the additives are isodecanol polyoxyethylene ether content is 2.5 mg / L, the content of diethylene glycol is 7.5 mg / L, the content of polydimethyldiallyl ammonium chloride is 12.5 mg / L, and the molecular weight of polydimethyldiallyl ammonium chloride is 100,000; the pH value is 4.

[0085] The surface morphology of the diamond wire prepared according to Comparative Example 4 is as follows Figure 7 As shown by Figure 7 It can be seen that the surface coating of the diamond wire prepared is smooth and bright overall, and there are many agglomerates on the surface of the diamond wire, but the size of the agglomerates is small, so the distribution uniformity of the sand on the surface of the diamond wire prepared in this embodiment is average. In general, lowering the pH of the plating solution has a negative impact on the sanding of the metallized diamond particles in Comparative Example 4. In fact, in a large number of our experiments, the pH of the plating solution is more acidic, and the quality and quantity of the sanding of the metallized diamond particles will decrease to varying degrees.

[0086] Comparative Example 5

[0087] The same operation as in Example 3 was carried out except that the molecular weight of the polydimethyldiallylammonium chloride in the additive was changed to 50,000.

[0088] The surface morphology of the diamond wire prepared according to Comparative Example 5 is as follows: Figure 8 As shown by Figure 8 It can be seen that the coating is smooth and bright overall, the amount of sand is large, the size of the agglomerates of particles on the surface of the diamond wire is small, and the uniformity of the sand is good. Figure 6 In comparison, changing and reducing the molecular weight of polydimethyldiallylammonium chloride in the compound additive described in Example 5 can still promote the sanding of metallized diamond, but the effect is lower than that of the compound additive solution in Example 5.

[0089] The hydrophilicity, Zeta potential and sand loading test results of Example 3 and Comparative Examples 4 and 5 are summarized in Table 2. Figure 6-8 shown.

[0090] Table 2 Comparison of hydrophilicity, zeta potential, amount of sand, and state of sand between Example 3 and Comparative Examples 4 and 5

[0091] Hydrophilicity(°) Zeta potential (mV) Sand quantity (grains / cm) Sanding status Example 3 53.5 17 1055 Excellent uniformity Comparative Example 4 57.7 21 599 Average uniformity Comparative Example 5 53.8 23 930 Good uniformity

[0092] It can be concluded from Table 2 that when the additive of Example 3 of the present invention is used, the hydrophilicity and Zeta potential of the metallized particles in the electroplating solution are improved, and the agglomeration of the metallized diamond particles on the surface of the wire saw is reduced; however, if the pH value of the electroplating solution used is lowered, such as to 4.0, the amount of sand on the diamond wire will drop significantly, indicating that when the additive of Example 3 is used, the pH value of the electroplating solution should be more alkaline. A large number of experiments have shown that the wire saw prepared with a plating solution pH value in the range of 4.65-4.85 has the best uniformity of sanding (in addition, the maximum pH value of the plating solution does not exceed 5.4); this rule applies to all additives in the present invention that have good sanding and dispersion effects. The molecular weight of the organic compound will also affect the amount of sand on the diamond particles. Compare Figure 6 and Figure 8 It can be seen that for the polydimethyldiallylammonium chloride in Example 3, if its molecular weight is changed from about 100,000 to about 50,000, the amount of sand applied will be reduced by about 11.8%.

[0093] Example 4

[0094] The formula of the upper sand plating solution in this embodiment is: 450g / L of nickel sulfamate, 3g / L of nickel chloride, 0.5g / L of basic nickel carbonate, 35g / L of boric acid, and the additive is a composite additive formula consisting of hydroxypropane sulfonate pyridinium salt and fatty alcohol polyoxyethylene ether, wherein the content of hydroxypropane sulfonate pyridinium salt is 25mg / L, and the content of fatty alcohol polyoxyethylene ether is 5mg / L; the pH value is 4.75.

[0095] In this embodiment, a steel wire with a diameter of 100 μm is selected as a busbar, metallized diamond particles coated with a nickel layer are selected as second phase particles, the content of the metallized diamond particles is 0.2 g / L, and the electroplating liquid system configured in Example 1 is used for the electroplating process.

[0096] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Fig. 9 As shown by Fig. 9 It can be seen that the coating is smoother and brighter overall, but the amount of sanding on the prepared diamond wire is small. In general, this embodiment is not conducive to improving the quality of sanding, and only improves the flatness and brightness of the coating on the surface of the diamond wire to a certain extent.

[0097] Example 5

[0098] The additives in Example 4 were replaced by a composite additive formula consisting of polyacrylamine hydrochloride and fatty alcohol polyoxyethylene ether, wherein the content of polyacrylamine hydrochloride was 2.5 mg / L and the content of fatty alcohol polyoxyethylene ether was 12.5 mg / L. Other than that, the same operation as in Example 4 was performed.

[0099] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Fig.10 As shown by Fig.10 It can be seen that the coating is smooth and bright overall, there is a large amount of sand on the surface of the diamond wire, there are fewer points of agglomeration, and the overall sand distribution is well uniform.

[0100] Example 6

[0101] Replace the additives in Example 4 with a composite additive formula consisting of polyacrylamine hydrochloride, fatty alcohol polyoxyethylene ether and polydimethyldiallyl ammonium chloride, wherein the content of polyacrylamine hydrochloride is 5 mg / L of the plating solution, the content of fatty alcohol polyoxyethylene ether is 2.5 mg / L of the plating solution, and the content of polydimethyldiallyl ammonium chloride is 10 mg / L of the plating solution. Other than this, the same operations as in Example 4 are performed.

[0102] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Fig.11 As shown by Fig.11 It can be seen that the coating is smooth and bright overall, there is a lot of sand on the surface of the diamond wire, the number of points where agglomerates appear has increased, the size of the agglomerates is not large, and the agglomeration is not serious overall, and the sand distribution is uniform.

[0103] The hydrophilicity, Zeta potential and sand loading test results of Examples 4 to 6 are summarized in Table 3. Figure 9-11 shown.

[0104] Table 3 Comparison of hydrophilicity, zeta potential, amount of sand, and state of sand in Examples 4 to 6

[0105] Hydrophilicity(°) Zeta potential (mV) Amount of sand (grains) Sanding status Example 4 56.7 0.3 100 Poor uniformity Example 5 53.5 54.3 528 Good uniformity Example 6 52.1 53.45 606 Good uniformity

[0106] From Table 3 and the attached Figure 9-11 It can be seen that the compound additive composed of hydroxypropane sulfonic acid pyridinium salt and fatty alcohol polyoxyethylene ether has little effect on the sanding of diamond particles, while the compound additive composed of polyacrylamine hydrochloride and fatty alcohol polyoxyethylene ether and the compound additive composed of polyacrylamine hydrochloride, fatty alcohol polyoxyethylene ether and polydimethyldiallyl ammonium chloride are beneficial to the sanding and can significantly improve the effect of sanding. Although it is not necessarily completely proportional and there are exceptions, in general, the better the hydrophilicity and the higher the Zeta point, the better the sanding effect and the better the particle dispersion, which is also true for the use of a single additive.

[0107] Example 7

[0108] Instead of the additive composite formula in Example 4, an additive composite formula consisting of octadecyltrimethylammonium bromide, polyethylene glycol and isodecanol polyoxyethylene ether was added, wherein the octadecyltrimethylammonium bromide content was 10 mg / L, the polyethylene glycol content was 2.5 mg / L, and the isodecanol polyoxyethylene ether content was 7.5 mg / L. Other than this, the same operations were performed as in Example 4.

[0109] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Fig.12 As shown by Fig.12 It can be seen that the diamond wire coating is smooth and bright, and the brightness is slightly reduced due to the large amount of sanding. The surface of the diamond wire prepared in this embodiment has many agglomeration points due to the high amount of sanding, but the size of the agglomeration is relatively small, and the agglomeration phenomenon is not serious. Overall, the distribution uniformity of the sanding in this embodiment is good.

[0110] Example 8

[0111] Instead of the additive composite formula in Example 4, an additive composite formula consisting of potassium aluminum sulfate dodecahydrate, triethanolamine, sodium benzoate and fatty alcohol polyoxyethylene ether was added, wherein the content of potassium aluminum sulfate dodecahydrate was 12.5 mg / L, the content of triethanolamine was 7.5 mg / L, the content of sodium benzoate was 10 mg / L, and the content of fatty alcohol polyoxyethylene ether was 5 mg / L. Other than this, the same operations were performed as in Example 4.

[0112] The surface morphology of the diamond wire prepared according to this embodiment is as follows: Fig.13 As shown by Fig.13 It can be seen that wrinkles appear in a small area of ​​the diamond wire coating, but the whole is relatively smooth and bright. The diamond wire prepared in this embodiment has a large amount of sand, and there are many places where slight agglomeration occurs. The agglomeration size is small and the degree is not serious. In general, the sand distribution uniformity of this embodiment is good.

[0113] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. An additive for diamond wire composite electroplating second phase particles, characterized in that: The additive is one or more of 3,3,4,4-tetramethylpyrrolidine-2,5-dione, polyethylene glycol, triethanolamine, polyacrylamide, glycine, hexadecyltrimethylammonium chloride, octadecyltrimethylammonium bromide, sodium dodecylbenzenesulfonate, hydroxypropanesulfonic acid pyridinium salt, polyacrylamine hydrochloride, isodecanol polyoxyethylene ether, fatty alcohol polyoxyethylene ether, sodium benzoate, polydimethyldiallylammonium chloride, polyvinyl alcohol, diethylene glycol, potassium aluminum sulfate dodecahydrate, and diphenylsulfonimide.

2. The additive for diamond wire composite electroplating second phase particles according to claim 1, characterized in that: The additive is polyacrylamine hydrochloride or 3,3,4,4-tetramethylpyrrolidine-2,5-dione, Polyacrylamine hydrochloride mass percentage 0%-0.5% or The mass percentage of 3,3,4,4-tetramethylpyrrolidine-2,5-dione is 0%-0.5%.

3. The additive for diamond wire composite electroplating second phase particles according to claim 1, characterized in that: The additive is composed of isodecanol polyoxyethylene ether, diethylene glycol and polydimethyldiallylammonium chloride. The mass percentage of isodecanol polyoxyethylene ether is 0%-0.2%; The mass percentage of diethylene glycol is 0%-0.1%; The mass percentage of polydimethyldiallylammonium chloride is 0%-0.5%.

4. The additive for diamond wire composite electroplating second phase particles according to claim 1, characterized in that: The additive is composed of hydroxypropane sulfonic acid pyridinium salt and fatty alcohol polyoxyethylene ether. The mass percentage of hydroxypropane sulfonic acid pyridinium salt is 0%-0.2%; The mass percentage of fatty alcohol polyoxyethylene ether is 0%-0.1%.

5. The additive for diamond wire composite electroplating second phase particles according to claim 1, characterized in that: The additive is composed of polyacrylamine hydrochloride and fatty alcohol polyoxyethylene ether. Polyacrylamine hydrochloride accounts for 0%-0.25% by mass; The mass percentage of fatty alcohol polyoxyethylene ether is 0%-0.5%.

6. The additive for diamond wire composite electroplating second phase particles according to claim 1, characterized in that: The additive is composed of polyacrylamine hydrochloride, fatty alcohol polyoxyethylene ether and polydimethyldiallylammonium chloride. Polyacrylamine hydrochloride accounts for 0%-0.6% by mass; Fatty alcohol polyoxyethylene ether accounts for 0%-0.3% by mass; The mass percentage of polydimethyldiallylammonium chloride is 0%-0.5%.

7. The additive for diamond wire composite electroplating second phase particles according to claim 1, characterized in that: The additive is composed of octadecyl trimethyl ammonium bromide, polyethylene glycol and isodecanol polyoxyethylene ether. Octadecyltrimethylammonium bromide accounts for 0%-0.2% by mass; Polyethylene glycol accounts for 0%-0.2% by mass; The mass percentage of isodecanol polyoxyethylene ether is 0%-0.5%.

8. The additive for diamond wire composite electroplating second phase particles according to claim 1, characterized in that: The additive is composed of potassium aluminum sulfate dodecahydrate, triethanolamine, sodium benzoate and fatty alcohol polyoxyethylene ether. Potassium aluminum sulfate dodecahydrate accounts for 0%-0.5% by mass; Triethanolamine accounts for 0%-0.3% by mass; Sodium benzoate accounts for 0%-0.25% by mass; The mass percentage of fatty alcohol polyoxyethylene ether is 0%-0.2%.

9. An electroplating solution comprising the additive, characterized in that: The electroplating solution is a nickel sulfamate nickel plating system, and its formula is: nickel sulfamate content 250-540 g / L, nickel chloride content 2-35 g / L, basic nickel carbonate content 0.5-15 g / L, boric acid content 30-45 g / L, saccharin content 0-5 g / L, pH value 3.5-5.3, and the content of the additive in the electroplating solution is 0-0.6%.

10. A method for preparing an electroplating solution containing the additive, characterized in that: The following steps are involved: (1) dissolving the additive into an additive solution; (2) Add nickel sulfamate and nickel chloride into 55-70°C deionized water, and heat and stir until completely dissolved; (3) Heat boric acid and deionized water to 70-90°C, stirring while heating until all are dissolved, then pour the boric acid solution into the dissolved nickel solution (2) and stir evenly; (4) Take basic nickel carbonate and deionized water, heat and stir for 5 min, then filter and add the filtered solution to the solution prepared in (3); (5) Add saccharin to the solution prepared in (4), heat to 55-70°C, and stir while heating until completely dissolved; (6) Use ammonia and aminosulfonic acid to adjust the pH value, and then add deionized water to the required amount of plating solution to control the pH value to 3.5-5.3; the preferred pH range is 4.65-4.85; (7) The additive solution is added to the electroplating solution prepared in (6), and stirred while heating until the mixture is uniformly mixed, thereby preparing an electroplating solution containing the additive.